Mechanistic modeling of ligand density variations on anion exchange chromatography. Issue 4 (30th December 2020) - Sanchez‐Reyes, Gabriela; Graalfs, Heiner; Hafner, Mathias; Frech, Christian
Abstract: Ion exchange chromatography is a powerful and ubiquitous unit operation in the purification of therapeutic proteins. However, the performance of an ion‐exchange process depends on a complex interrelationship between several parameters, such as protein properties, mobile phase conditions, and chromatographic resin characteristics. Consequently, batch variations of ion exchange resins play a significant role in the robustness of these downstream processing steps. Ligand density is known to be one of the main lot‐to‐lot variations, affecting protein adsorption and separation performance. The use of a model‐based approach can be an effective tool for comprehending the impact of parameter variations (e.g., ligand density) and their influence on the process. The objective of this work was to apply mechanistic modeling to gain a deeper understanding of the influence of ligand density variations in anion exchange chromatography. To achieve this, 13 prototype resins having the same support as the strong anion exchange resin Fractogel ® EMD TMAE (M), but differing in ligand density, were analyzed. Linear salt gradient elution experiments were performed to observe the elution behavior of a monoclonal antibody and bovine serum albumin. A proposed isotherm model for ion exchange chromatography, describing the dependence of ligand density variations on protein retention, was successfully applied.